Attitudes of Turkish students towards markets: are they different from their Western counterparts? - ÇOKGEZEN, MURAT (SPRINGER, 2017)
This study evaluates attitudes of Turkish university students towards markets and the influence on these attitudes of studying in economics. It is found that university students taking economics courses in Turkey have negative opinions about the justice of market relations, and that, unlike in the case of students in other countries, in Turkey, 4 years of study in an economics department does not change this. These results are in contradiction with the findings of other studies on Western students.
Keywords: Economists; Fairness; Learning; Attitudes; UNITED-STATES